POLITICAL PARTY STRATEGIES IN ELECTION 2024 IN SINGKAWANG CITY (CASE STUDY OF PDIP AND PKB) - Anugrah, Akhmad Rifky Setya (Journal of Social Politics and Governance (JSPG), 2024)
Simultaneous elections in 2024 are a democratic party agenda that is held every five years. This research aims to describe how political party strategies are preparing for the 2024 elections. In 2017, PDIP and PKB were the two winning parties in the singkawang city regional head election. These two parties each have a large mass support base in Singkawang city also more important were the 1st and 2nd winner of general election 2024 that will be the object of this research that will be the object of this research. By using a qualitative approach, namely through in-depth interviews for primary data and and using secondary data sources such as news, journal articles and documentation to obtain complete data. Data analysis is carried out by filtering information and validating data by triangulating sources with the aim of increasing the validity and reliability of research results. The author found that both parties have their own strategies in an effort to win the 2024 elections, namely through offensive and defensive strategies. Offensive strategies are strategies that focus on expanding the voter market while defensive strategies are more about internal party strengthening and coordination.